The Culture Gap: An Analysis of Source, Target, and Global Culture Representation in Indonesian English Teaching Textbooks - Jismulatif, Jismulatif; Putri, Syadza Adila (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2023)
Most Indonesian educators are insufficient to address the importance of educating students about other cultures. This problem emerges as a result of foreign language teachers' lack of understanding of how to incorporate culture into language acquisition, particularly in English. This research aims to investigate culture's representation and examine the culture introduced in Indonesian textbooks for senior high school students who learn English as a foreign language. Employing a qualitative descriptive approach with an intercultural perspective, the study systematically analyzes the cultural content and themes present in three Electronic English teaching textbooks: Bahasa Inggris X, Bahasa Inggris IX, and Bahasa Inggris XI revised edition (2017) by Kemdikbud RI. The analysis of the textbooks' contents is conducted using the framework developed by Cortazzi and Jin (1999), specifically focusing on Source Culture, Target Culture, and International Culture. These textbooks were selected as they are widely used in Indonesian senior high schools and are published by the Indonesian Ministry of Education and Culture. The findings of the study reveal that the dominance of source culture content is significant, while the representation of target culture and international culture is considerably low. Furthermore, among the 19 cultural motifs categorized as Big Culture and Little Culture, the prevalence of Little Culture themes is most notable. The findings of this research shed light on the existing disparity and call for a more comprehensive approach to cultural education in English language learning. By acknowledging the imbalance and addressing the representation of different cultures, educators can better equip students with intercultural competence and foster a deeper understanding of diverse cultural perspectives.